POSSIBILITIES OF NANOTECHNOLOGIES IN THE CREATION OF NEW DEVICES AND MATERIALS (Web of Technology: Multidimensional Research Journal, 2023)
The paper provides an overview of the emergence of nanotechnologies that make it possible to create the latest materials with unique properties, control their properties at the atomic and molecular levels, and ensure the production of a wide variety of technical devices, as well as microchips with a size of less than 100 nanometers.